Improving Student Attitudes and Academic Performance in Introductory Biology Using a Project-Based Learning Community - Tyesha N. Burks (Journal of Microbiology & Biology Education, 2022)
ABSTRACT Students majoring in non-STEM fields often identify introductory biology courses as irrelevant and overly rigorous. Resistance to enroll in a required general education science course, coupled with negative attitudes toward the subject, can adversely affect the academic performance of students; this can especially be present in students from under-represented minority groups. Therefore, instructors have to intentionally design a curriculum that overcomes these factors as they educate non-major students enrolled in introductory biology. BioArt, a learning community, was formed between introductory biology and introduction to graphic design courses to improve the attitudes and academic performance of students in the biology course at a Historically Black College and University (HBCU). The BioArt model incorporated a common theme, project-based learning, and opportunities for experiential learning. To measure outcomes, traditional examinations, non-traditional assessments, failure/withdraw rates, and student attitudes were evaluated. Using this model, introductory biology became less intimidating, more relevant, and improved academic success among freshman minority students. Thus, the BioArt model can be utilized as an intervention at different institutions of higher learning.